Some New Fixed-Point Theorems for a (ψ, ϕ)-Pair Meir-Keeler-Type Set-Valued Contraction Map in Complete Metric Spaces. (26th December 2011) - Chen, Chi-Ming
Abstract : We obtain some new fixed point theorems for a (ψ, ϕ )-pair Meir-Keeler-type set-valued contraction map in metric spaces. Our main results generalize and improve the results of Klim and Wardowski, (2007).